Pengaruh Servant Leadership Dan Empowerment Terhadap Organizational Citizenship Behavior Dengan Disiplin Kerja Sebagai Variabel Intervening (Studi Pada PT. EMPAT PUTERA UTAMA BERSAMA SURABAYA) - Erga Renata Sabila; Mochammad Isa Anshori (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
The current digital era encourages competition in all fields. One of them is the service industry in the tourism sector, namely rail transportation. Under these conditions, human resources are required to run well in order to increase the effectiveness and efficiency of the KAI company. PT. EMPAT PUTERA UTAMA BERSAMA SURABAYA has employees where the employees are human resources who have individual behavior or interpersonal skills that belong to a scope known as Organizational Citizenship Behavior aimed at improving the quality of the company. This study has an objective to determine the effect of servant leadership and empowerment on organizational citizenship behavior through work discipline as an intervening variable at PT. EMPAT PUTERA UTAMA BERSAMA SURABAYA. The results of this study indicate that servant leadership has no significant effect on organizational citizenship behavior because the lack of a leader's role in showing more attention to all employees and is considered to be different from one employee to another employee in the company. Empowerment has a significant effect on organizational citizenship behavior. Servant leadership has a significant effect on the mediating variable, namely work discipline. Empowerment has a significant effect on work discipline. Work discipline has a direct effect on organizational citizenship behavior.